Six-Year Changes in Physical Activity and the Risk of Incident Heart Failure: ARIC Study. Issue 20 (15th May 2018) - Florido, Roberta; Kwak, Lucia; Lazo, Mariana; Nambi, Vijay; Ahmed, Haitham M.; Hegde, Sheila M.; Gerstenblith, Gary; Blumenthal, Roger S.; Ballantyne, Christie M.; Selvin, Elizabeth; Folsom, Aaron R.; Coresh, Josef; et al.
Abstract : Background: Higher physical activity (PA) is associated with lower heart failure (HF) risk; however, the effect of changes in PA on HF risk is unknown. Methods: We evaluated 11 351 ARIC study (Atherosclerosis Risk in Communities) participants (mean age 60 years) who attended visit 3 (1993–1995) and did not have a history of cardiovascular disease. Exercise PA was assessed using a modified Baecke questionnaire and categorized according to American Heart Association guidelines as recommended, intermediate, or poor. We used Cox regression models to characterize the association of 6-year changes in PA between the first (1987–1989) and third ARIC visits and HF risk. Results: During a median of 19 years of follow-up, 1750 HF events occurred. Compared with those with poor activity at both visits, the lowest HF risk was seen for those with persistently recommended activity (hazard ratio, 0.69; 95% confidence interval, 0.60–0.80). However, those whose PA increased from poor to recommended also had reduced HF risk (hazard ratio, 0.77; 95% confidence interval 0.63–0.93). Among participants with poor baseline activity, each 1 SD higher PA at 6 years (512.5 METS*minutes/week, corresponding to ≈30 minutes of brisk walking 4 times per week) was associated with significantly lower future HF risk (hazard ratio, 0.89, 95% confidence interval, 0.82–0.96). Conclusions: Although maintaining recommended activity levels is associated with the lowest HF risk, initiating and increasing PA, even in late middle age, are also linked to lower HF risk. Augmenting PA may be an important component of strategies to prevent HF. Abstract : Supplemental Digital Content is available in the text.